2009
DOI: 10.1007/s00535-009-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HCV-associated gene expression and cell signaling pathways in cells with or without HCV replicon and in replicon-cured cells

Abstract: Comprehensive gene expression and pathway analyses show that lipid biosynthesis pathways are crucial to support proficient virus replication. These metabolic pathways could constitute novel antiviral targets against HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 48 publications
6
28
1
Order By: Relevance
“…In this study, host genes involved in cellular metabolism and intracellular transport were also significantly regulated by JFH-1 infection. Although previous studies have shown that HCV can alter lipid metabolism (32), this study demonstrated that genes involved in protein synthesis and degradation, posttranslational modification, vesicle trafficking, and cytoskeleton function are also regulated following infection.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…In this study, host genes involved in cellular metabolism and intracellular transport were also significantly regulated by JFH-1 infection. Although previous studies have shown that HCV can alter lipid metabolism (32), this study demonstrated that genes involved in protein synthesis and degradation, posttranslational modification, vesicle trafficking, and cytoskeleton function are also regulated following infection.…”
Section: Discussioncontrasting
confidence: 63%
“…Many of the genes selected were regulated in a highly coordinated manner (e.g., cholesterol biosynthesis genes, tRNA synthetase genes, and metallothionein genes), indicating that the regulation of these genes may significantly impact cellular function. By comparing the findings of this study to previously published HCV microarray studies, overlapping expression patterns were observed, including the regulation of genes involved in proliferation, apoptosis, cytokine and chemokine production, and lipid metabolism (1,2,32,53). However, many novel host genes regulated by HCV infection were also identified, including those involved in protein synthesis and degradation, posttranslational modification, and vesicular trafficking.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Such patients show higher levels of hepatic SOCS3 ex- pression than those without obesity or insulin resistance (34,61). We reported previously that a series of genes involved in fatty acid and cholesterol synthesis are upregulated in HCV replicon-expressing and HCV-JFH1-infected cells and increased cellular LDs (39). Such lipogenic cellular processes may be the cause of the upregulated expression of IL-6.…”
Section: Discussionmentioning
confidence: 99%